2001
DOI: 10.1007/bf02707265
|View full text |Cite
|
Sign up to set email alerts
|

The demand for M3 and inflation forecasts: An empirical analysis for Switzerland

Abstract: E5, E41, E47,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…The analysis of Kirchgässner and Wolters (2009, KW henceforth) corroborates the findings of Baltensperger, Jordan and Savioz (2001), 1 who find compelling evidence for M3 as information variable in the Swiss monetary policy process. Using data covering the period from 1983 to 2008, KW extend the analysis and estimate money demand equations for the monetary aggregates M1, M2 and M3.…”
Section: Basic Conclusion Of the Papersupporting
confidence: 75%
“…The analysis of Kirchgässner and Wolters (2009, KW henceforth) corroborates the findings of Baltensperger, Jordan and Savioz (2001), 1 who find compelling evidence for M3 as information variable in the Swiss monetary policy process. Using data covering the period from 1983 to 2008, KW extend the analysis and estimate money demand equations for the monetary aggregates M1, M2 and M3.…”
Section: Basic Conclusion Of the Papersupporting
confidence: 75%
“…Brüggemann, 2003), Spain (Juselius and Toro, 2006) and the United Kingdom (Dhar, Pain and Thomas, 2000;Garratt, Lee, Pesaran and Shin, 2003). Baltensperger, Jordan and Savioz (2001) estimate a cointegrated VAR model for Switzerland comprising nominal M3, real gross domestic product (GDP), the GDP deflator and the government bond yield. Imposing a longrun money demand function and using a Choleski decomposition to identify monetary policy shocks, they find that the residuals from the long-run money demand equation help forecast inflation.…”
Section: Related Literaturementioning
confidence: 99%
“…Several studies have suggested that estimates of income elasticity are biased upward through the use of the incorrect scale variable for broad money demand. Kristen-Gerlach (2001) and Baltensperger et al (2001) argue that wealth rather than GDP income is the preferred variable. Others such as Peytrignet (1996) suggest that problems of a high income elasticity stem from improper price indices.…”
Section: Appendix: Time Series Results With Aggregate Cross-cantonal mentioning
confidence: 99%
“…This redefines the research agenda for Swiss money demand. If the new cross-cantonal estimates are accepted, it is no longer necessary to rely on conjectures of family decomposition (see Mulligan and Sala-i-Martin, 1992), the use of the correct scale variable (Baltensperger et al 2001), or backward bending labor supply curves (Mankiw, 1992) to justify income elasticities greater than one. While such hypotheses enjoy considerable appeal among many economists, the support for such explanations rests on weak empirical foundations in Switzerland.…”
Section: Summary and Policy Implicationsmentioning
confidence: 99%